PENERAPAN METODE DIRECT SEARCH PADA SISTEM INFORMASI SEJARAH PAHLAWAN SULAWESI SELATAN BERBASIS ANDROID - Pujianti Wahyuningsih; Nur Mustika (LPPM Poltek ST Paul, 2020)
The necessary of young generation knowledge about the Indonesian hero’s history is very important to grow their nationalism, especially the young generation in the South Sulawesi of Indonesia. One of the ways can be used to grow the nationalism of the young generation are by utilization of Android technology to give information about the history of Indonesian heroes. The purpose of this study is to build the information system of Indonesian heroes based on Android using direct search method. The direct search method is the method is able to use to search the information by directly to solve the problem without need additional information. The result of this study is the information system was developed is able to use to the society to give the information about the national hero history especially in the South Sulawesi of Indonesia.